Tingkat prevalensi dan intensitas ektoparasit pada benih ikan Nila (Oreochromis niloticus) - Prislawati Paputungan; Reni L. Kreckhoff; Reiny A. Tumbol; Ockstan J. Kalesaran; Juliaan Ch. Watung; Suzanne L. Undap (Universitas Sam Ratulangi, 2023)
This study aims to inventory the types of parasites that exist in the Center for Development and Development of Tateli Fish Farming (BP2HPI) Tateli. This research was conducted in April-July 2023 at BP2HPI, Tateli as the location for sampling 30 tilapia (Oreochromis niloticus) seeds randomly in 3 nursery ponds, and then brought to the Laboratory of Aquaculture Technology FPIK Unsrat for parasite observations. Before examining the fish parasites, the sample is put into a bucket filled with water and given aeration so that the fish are still alive during the inspection. In this research activity, several water quality parameters were also measured, namely temperature, pH, and DO in situ. The procedure for examining ectoparasites refers to the procedure according to Kabata (1985). Parasite examination begins with observing the outside of the body, and taking notes if abnormal signs are found such as swelling, bleeding, the presence of black or white spots on the surface of the body, or changes in body color, then the presence of parasites is examined using a microscope with 400x magnification. The examination found 2 types of parasites that infect the seeds of tilapia (Oreochromis niloticus) at the Center for Development and Control of Fish Pests and Diseases (BP2HPI), Tateli are Ttrichodina sp and Gyrodactylus sp. The prevalence of parasites that attack tilapia seeds as a whole reaches 100% which is divided into 90% Trichodina sp and 10%, Gyrodactylus sp. Keywords: parasitic infestation, fish disease, water quality, aquaculture